The Optimizing Sponsorship Strategies for Music Concerts: Insights from 'Nyanyian Riang Gembira 2023’ - Putri, Rachmayani; Agus Priyanto, Wisanggeni; Hasan, Hanif (Politeknik Pariwisata NHI Bandung, 2025)
Sponsorship plays a fundamental role in the success of events by providing financial, service, and product support. This study aims to explore sponsorship activities and strategies for their development at the Nyanyian Riang Gembira 2023 event organized by CV Endless Creative Production. A qualitative research approach was used, incorporating data collection methods such as interviews, observations, and documentation. The analysis was conducted using five stages: SOAR analysis, data reduction, data presentation, conclusion drawing, and triangulation. The findings indicate that while CV Endless Creative Production has made significant efforts in sponsorship management, the implementation remains suboptimal, particularly due to the absence of a specialized sponsorship strategy. The study highlights that the sponsorship development strategy is essential for brand recognition, strengthening relationships with sponsors, achieving sponsorship targets, and establishing a structured sponsorship framework. These findings emphasize the need for a more systematic approach to sponsorship acquisition and management to enhance event sustainability and financial stability.